A review of the short- and long-term impact of weight loss on appetite in youth: what do we know and where to from here?. Issue 3 (10th August 2020) - Truby, Helen; Bennett, Christie; Martins, Catia
Abstract : This review seeks to synthesise our knowledge about changes in hunger and satiety that occur during diet-induced weight loss and during weight loss maintenance, with a particular focus on youth with obesity. Mechanisms of appetite responses to weight loss rely heavily on the adult literature. Physiological mechanisms that control appetite and satiety via the gut–brain axis have been elucidated but we have an incomplete picture of changes in gut hormones and peptides in youth with obesity. In adolescents, the role of the brain in long-term sensing of body composition and modifying appetite and satiety changes is easily over-ridden by hedonic influences for the reward of highly palatable sweet foods and encourages over-consumption. Accordingly, reward cues and hyper-responsiveness to palatable foods lead to a pattern of food choices. Different reward systems are necessary that are substantial enough to reward the continued individual effort required to sustain new behaviours, that need to be adopted to support a reduced body weight. Periods of growth and development during childhood provide windows of opportunity for interventions to influence body weight trajectory but long-term studies are lacking. More emphasis needs to be placed on anticipatory guidance on how to manage powerful hedonic influences of food choice, essential to cope with living in our obesogenic environment and managing hunger which comes with the stronger desire to eat after weight has been lost.